Programs and Schedule - Marty White (Symphony in the Flint Hills, 2009)
The schedule of activities, program notes and information about the Kansas City Symphony, Conductor Steven Jarvi, and other details of the Symphony in the Flint Hills for the 4th annual concert 2009.
Keywords: schedule; program; concert; biographical notes; Kansas City Symphony